2015
DOI: 10.1098/rspa.2014.0772
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the actual nonlinear slope geometry for catastrophic failure in submarine landslides

Abstract: A simple approach to slope stability analysis of naturally occurring, mild nonlinear slopes is proposed through extension of shear band propagation (SBP) theory. An initial weak zone appears in the steepest part of the slope where the combined action of gravity and seismic loads overcomes the degraded peak shear resistance of the soil. If the length of this steepest part is larger than the critical length, the shear band will propagate into the quasi-stable parts of the slope, where the gravitational and seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…(6) increases and can, in principle, exceed the current length of the slip surface. Puzrin et al (2015) have shown that if the slip surface starts propagating, it will always reach the boundaries of the quasi-stable zone, as long as the average shear stress ratio r remains positive (always true within the quasi-stable zone, where r > 0). This is, of course, assuming that excess porewater pressures and the degradation index do not change during slip surface growth.…”
Section: Unstable Growth Of Slip Surfaces In Quasi-stable Zonementioning
confidence: 99%
See 4 more Smart Citations
“…(6) increases and can, in principle, exceed the current length of the slip surface. Puzrin et al (2015) have shown that if the slip surface starts propagating, it will always reach the boundaries of the quasi-stable zone, as long as the average shear stress ratio r remains positive (always true within the quasi-stable zone, where r > 0). This is, of course, assuming that excess porewater pressures and the degradation index do not change during slip surface growth.…”
Section: Unstable Growth Of Slip Surfaces In Quasi-stable Zonementioning
confidence: 99%
“…1). For a curved slope, Puzrin et al (2015) have demonstrated that the initial slip surface formed in the unstable zone (r > 1) will propagate catastrophically (i.e., under existing external forces) into the quasi-stable zone (r > 0) if its initial length, L i , exceeds the critical value…”
Section: Unstable Growth Of Slip Surfaces In Quasi-stable Zonementioning
confidence: 99%
See 3 more Smart Citations